Evaluation of Thompson Seedless and its Clone Based on Fruit Characteristics under Indian Condition - Nale, R. D.; Somkuwar, R. G.; Ghatul, I. D.; Mulani, Saklain (International Journal of Bio-resource and Stress Management, 2025)
The present study was conducted during fruiting season during October, 2023 to April, 2024 at the experimental farm of ICAR-National Research Centre for Grapes, Pune, Maharashtra, India to evaluate clones for fruit morphology by multivariate analysis and estimate similarity distances among different clones. In this study, 13 clones belonging to Thompson Seedless (Tas-A-Ganesh, Manik Chaman, Sonaka, Maruti Seedless, Ambe Seedless, SSN, Sudhakar Seedless, Pusa Seedless, 2A clone and H-5-Clone) were characterized considering pomological diversity under Indian conditions. A total of 15 berry and bunch attributes were characterized in clones for the distinctness. A high variability (60.38%) was found in the evaluated grape cultivars, and significant differences were found between them in all fruit attributes. The morphological quantitative traits such as bunch weight, bunch length, berry weight, number of berries bunch-1, berry diameter, berry length and TSS were in following range 62.13–224.67 g, 8.0–17.50 cm, 46.0–127.0 g, 60.0–154.0, 7.50–15.87 mm, 11.30–19.24 mm and 18.0–22.4 °Brix respectively which indicated a wide level of diversity in the clonal varieties. There were high positive correlations between bunch and berry traits particularly weight and length while negative correlation between total soluable solid (TSS) and titratable acidity (TA). Principal component analyses showed a considerable fruit diversity in the studied grape varieties. Clonal selection and conservation of the highly diverse autochthonous grapes are therefore recommended.